Role of “Zamana” Premchand Number In Prem Chand Shanasi - Bashir, Saba; Gondal, Ghulam Abbas (sourcecoder, 2023)
Prem chand was a renowned Urdu novelist and short story writer. His portrait social as well as political aspect of his era in his creations. Class discrimination was very high in his era. He became the voice of oppressed class .In this way he set a good example of social realism. Therefore his creative work was acknowledged even his era. Many journals published articles of different critics about PREM CHAND SHANASI. “ZAMANA” also published a special PREM CHAND NUMBER. Through this article an attempt has been made to know about the role of ZAMANA PREM CHAND NUMBER in the field of PREM CHAND SHANASI.